2007
DOI: 10.1002/jmv.20899
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of β‐ and γ‐herpesviruses within Waldeyer's ring organs

Abstract: The Waldeyer's ring designates a functional unit of lymphoid tissue within the pharynx including the adenoids and tonsils. To gain insight into distribution patterns of beta- and gamma-human herpesviruses (HHVs) and their potential mutual influences at their natural portal of entry, quantitative polymerase chain reaction (qPCR) assays were applied to adenoids and tonsils obtained from 30 children. DNA of Epstein-Barr virus (EBV), cytomegalovirus (CMV), HHV-6, HHV-7, and HHV-8 was detected in adenoids, tonsils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 17 publications
9
28
0
Order By: Relevance
“…Although the pathogenetic effect exerted by HHV-6 in human lymphoid tissue ex vivo was demonstrated, the findings of a recent study showed that herpesvirus (HHVs) infection including HHV-6, exhibit a distinct distribution in the Waldeyer's ring organs suggesting that HHVs may contribute to the severity of disease especially in immunocompromised children [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…Although the pathogenetic effect exerted by HHV-6 in human lymphoid tissue ex vivo was demonstrated, the findings of a recent study showed that herpesvirus (HHVs) infection including HHV-6, exhibit a distinct distribution in the Waldeyer's ring organs suggesting that HHVs may contribute to the severity of disease especially in immunocompromised children [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…Palatine tonsils, a secondary lymphoid organ triggering immune responses against inhaled or ingested microorganisms, may serve as a reservoir for several HHV species. Indeed, previous studies reported the detection of HSV1, EBV, CMV, HHV6, HHV7, and KSHV in tonsil specimens . Of particular interest, data on Waldeyer's ring infection with EBV are crucial, as a recognized cause of nasopharyngeal carcinoma and lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted using the QIAmp DNA mini kit (Qiagen, Hilden, Germany). CMV DNA analysis was performed using the TaqMan real-time PCR technique as described earlier [9] . Several complementary investigations were performed in an attempt to rule out a congenital infection and to date the acquisition of the virus by the child.…”
Section: Case Reportmentioning
confidence: 99%